Is the section of verses 1-29 in Vākyapadīya III.3 based on a sound theoretical motivation? (2016)
The present article attempts to establish the following propositions:1. The remarks to be found in the initial segment of the so-called Saṃbandha-Samuddeśa (SS) of Bhartṛharti’s Vākyapadīya, or Trikāṇḍī, can be interpreted in a way which permits to regard them as the expression of a valid theoretical view. 2. It is important to investigate the possible existence of a sound theoretical motivation in philosophical treatises not only under the perspective of philosophical analysis but even in the framework of traditional textual exegesis irrespective of whether the textual sources represent a Western or a non-Western tradition of thought.